James B. Conant : Harvard to Hiroshima and the making of the nuclear age - Hershberg, James G. (Borzoi book, 1993)
James B. Conant was one of the giants of the American establishment. In this monumental biography, the first ever written, James G. Hershberg gives us the life of the renowned educator and scientist who led the U.S. government's effort to develop weapons of mass destruction, and whose own story mirrors America's transition from isolationism to global superpower at the dawn of the nuclear age. Here is the full scope of Conant's astonishing life. Born in a working-class suburb of Boston, he demonstrated a remarkable aptitude in science that won him the chance to study chemistry at Harvard, where academic distinction led to a professorship. Then, in 1933, when this son of a photoengraver seemed a likely prospect for a Nobel Prize, Conant tearfully left his laboratory to assume the presidency of Harvard, the pinnacle of American education